Coaching and developing the female swimmer - Sweetenham, B.; Goldsmith, W.; Morris, H. (1998)
On the specifics for training and working with female swimmers. - Resons for the opinion of the author that males and females should definitely train differently. - Positive considerations for a coach who wants to have success with coaching female swimmers, both during and after maturation. - Major differences in body size and composition between girls and boys and coaching implications. - Menstrual cycle and women-specific problems - Pregnancy, nutition, eating disorders, psychology.